Fetal obstructive uropathy complicated by urinary ascites: outcome and prognostic value of fetal serum β‐2‐microglobulin. (31st January 2013) - Spaggiari, E.; Dreux, S.; Czerkiewicz, I.; Favre, R.; Schmitz, T.; Guimiot, F.; Laurichesse Delmas, H.; Verspyck, E.; Oury, J.‐F.; Ville, Y.; Muller, F.
ABSTRACT: Objectives: To determine whether the prognostic value of fetal serum β ‐2‐microglobulin is altered and whether the occurrence of fetal urinary ascites prevents kidney damage in cases of fetal obstructive uropathy with urinary ascites. Methods: This was a retrospective study of cases of fetal bilateral obstructive uropathy that occurred between 2006 and 2010, for which both fetal serum and ascites samples were sent to our laboratory for analysis. β ‐2‐microglobulin was assayed in both fetal serum and the corresponding ascites. Renal outcome was analyzed. Histological features of the kidney in cases of termination of pregnancy and renal function of liveborn infants were recorded. Results: Fourteen cases with analysis of fetal serum and fetal ascites in a context of urinary obstruction were included. Renal outcome was unfavorable in eight cases (57%) and favorable in six (43%). When fetal serum β ‐2‐microglobulin was < 5 mg/L, renal outcome was favorable in all cases (4/4). When fetal serum β ‐2‐microglobulin was ≥ 5 mg/L, 8/10 cases (80%) had an unfavorable renal outcome (sensitivity, 100%; specificity, 66%). Conclusion: Fetal serum β ‐2‐microglobulin reliably predicts postnatal renal outcome in obstructive uropathy complicated by urinary ascites. Moreover, urine extravasation does not seem to protect fetal renal function.